FGF23 regulates renal sodium handling and blood pressure. Issue 6 (5th May 2014) - Andrukhova, Olena; Slavic, Svetlana; Smorodchenko, Alina; Zeitz, Ute; Shalhoub, Victoria; Lanske, Beate; Pohl, Elena E; Erben, Reinhold G
Abstract Fibroblast growth factor‐23 (FGF23) is a bone‐derived hormone regulating renal phosphate reabsorption and vitamin D synthesis in renal proximal tubules. Here, we show that FGF23 directly regulates the membrane abundance of the Na+:Cl− co‐transporter NCC in distal renal tubules by a signaling mechanism involving the FGF receptor/αKlotho complex, extracellular signal‐regulated kinase 1/2 (ERK1/2), serum/glucocorticoid‐regulated kinase 1 (SGK1), and with‐no lysine kinase‐4 (WNK4). Renal sodium (Na+) reabsorption and distal tubular membrane expression of NCC are reduced in mouse models of Fgf23 and αKlotho deficiency. Conversely, gain of FGF23 function by injection of wild‐type mice with recombinant FGF23 or by elevated circulating levels of endogenous Fgf23 in Hyp mice increases distal tubular Na+ uptake and membrane abundance of NCC, leading to volume expansion, hypertension, and heart hypertrophy in a αKlotho and dietary Na+‐dependent fashion. The NCC inhibitor chlorothiazide abrogates FGF23‐induced volume expansion and heart hypertrophy. Our findings suggest that FGF23 is a key regulator of renal Na+ reabsorption and plasma volume, and may explain the association of FGF23 with cardiovascular risk in chronic kidney disease patients.